Post-9/11/2001 lung function trajectories by sex and race in World Trade Center-exposed New York City emergency medical service workers. Issue 3 (3rd November 2016) - Vossbrinck, Madeline; Zeig-Owens, Rachel; Hall, Charles B; Schwartz, Theresa; Moir, William; Webber, Mayris P; Cohen, Hillel W; Nolan, Anna; Weiden, Michael D; Christodoulou, Vasilios; Kelly, Kerry J; Aldrich, Thomas K; et al.
Abstract : Objective: To determine whether lung function trajectories after 9/11/2001 (9/11) differed by sex or race/ethnicity in World Trade Center-exposed Fire Department of the City of New York emergency medical service (EMS) workers. Method: Serial cross-sectional study of pulmonary function tests (PFTs) taken between 9/11 and 9/10/2015. We used data from routine PFTs (forced expiratory volume in 1 s (FEV1 ) and FEV1 % predicted), conducted at 12–18 month intervals. FEV1 and FEV1 % predicted were assessed over time, stratified by sex, and race/ethnicity. We also assessed FEV1 and FEV1 % predicted in current, former and never-smokers. Results: Among 1817 EMS workers, 334 (18.4%) were women, 979 (53.9%) self-identified as white and 939 (51.6%) were never-smokers. The median follow-up was 13.1 years (IQR 10.5–13.6), and the median number of PFTs per person was 11 (IQR 7–13). After large declines associated with 9/11, there was no discernible recovery in lung function. In analyses limited to never-smokers, the trajectory of decline in adjusted FEV1 and FEV1 % predicted was relatively parallel for men and women in the 3 racial/ethnic groups. Similarly, small differences in FEV1 annual decline between groups were not clinically meaningful. Analyses including ever-smokers were essentially the same. Conclusions: 14 years after 9/11, most EMS workers continued to demonstrate a lack of lung function recovery. The trajectories of lung function decline, however, were parallel by sex and by race/ethnicity. These findings support the use of routine, serial measures of lung function over time in first responders and demonstrate no sex or racial sensitivity to exposure-related lung function decline.